The Relationship between Iranian EFL Teachers' Empowerment and Teachers' Self-efficacy. (13th May 2015) - Veisi, Shima; Azizifar, Akbar; Gowhary, Habib; Jamalinesari, Ali
Abstract: The present study focuses on the relationship between teacher empowerment and teacher self-efficacy. The research is a quantitative study in which the data is obtained to get a great understanding on the relationship between empowerment and self-efficacy of Iranian English as Foreign Language (EFL) teachers. The sample consisted of 60 teachers in Ilam and Eyvan high schools. Participants in this study answered the School Participant Empowerment Scale (SPES) questionnaire (Short and Rinehart, 1992 ). The Teacher Sense of Efficacy Scale (TSES) (Tschannen-Moran & Woolfolk Hoy, 2001) was used to measure teacher self-efficacy and differences in teachers on age, gender, and years of teaching experience. Pearson Product -Moment correlation was computed to determine the relationship between teacher empowerment and teacher self-efficacy. The findings indicated significant positive correlation between teacher empowerment and teacher self-efficacy. Independent sample t-test revealed no statistically significant differences on empowerment or self-efficacy based on age and empowerment based on years of teaching experience or gender. In addition, a statistically significant difference was found between teachers' self-efficacy and gender. The results of this study can be useful for EFL teachers and administrators.